PERILAKU MEROKOK DI KALANGAN REMAJA (STUDI KASUS LOKASI NONGKRONG DAERAH PANJER DENPASAR) - Naibaho, Leander F.; Zuryani, Nazrina; Kebayantini, Ni Luh Nyoman (JURNAL ILMIAH SOSIOLOGI (SOROT), 2020)
Teens is the moment when an individual begin to interact with people around them. As the advancement of technology these days, more and more teenagers become easier become influenced by information they received. This research is aimed for understanding the background and smoking habbit in teenagers aged 12-18 years old, also the agents who influence teenagers to smoke. The research took place in Circle K at Tukad Yeh Aya Street, Panjer Denpasar. Based on the theory of peer group by Charles Horton Cooley and by means of qualitative description this research is developed. All the data in this research was collected by interviewing group of teens, doing observation, and making documentation. The result is in the primary group the role of family, religion, economy, and are the main reason driving teenagers smoking, while in the secondary group agents influencing teen to smoke is their peers, milieu and source of information. Keywords: Pattern of Behavior, Smoking, Teenagers